2016
DOI: 10.1002/gps.4610
|View full text |Cite
|
Sign up to set email alerts
|

A transcultural cognitive marker of Alzheimer's Disease

Abstract: TB deficits may be conceived as a fundamental marker of AD. The Flash-card version is suitable for clinical use also in primary care facilities and in intervention trials, requires minimal training for administration and scoring, is quick to administer, non-invasive, inexpensive, and facilitates cross-cultural studies. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 67 publications
5
42
0
1
Order By: Relevance
“…Without titration and with high memory load, (Koppara et al, 2015) reported that such selectivity disappeared in MCI samples. However, when memory load is low, the selectivity of binding is restored in these MCI people and mirrors that found in patients with AD dementia (Sergio Della Sala et al, 2017).…”
Section: Why Dissecting Memory Binding Impairments Is Important?supporting
confidence: 65%
See 3 more Smart Citations
“…Without titration and with high memory load, (Koppara et al, 2015) reported that such selectivity disappeared in MCI samples. However, when memory load is low, the selectivity of binding is restored in these MCI people and mirrors that found in patients with AD dementia (Sergio Della Sala et al, 2017).…”
Section: Why Dissecting Memory Binding Impairments Is Important?supporting
confidence: 65%
“…Interestingly, a subgroup of controls (n=7) showed performance below a recently reported cut-off (Sergio Della Sala et al, 2017) despite an intact neuropsychological background.…”
Section: Why Dissecting Memory Binding Impairments Is Important?mentioning
confidence: 73%
See 2 more Smart Citations
“…A recent study has stressed on the cultural validity of the VSTM binding test (Della Sala et al, 2016). Here, we have shown that VSTM binding of features of everyday objects is preserved in older adults who have a low educational background.…”
Section: Discussionmentioning
confidence: 99%